Ticagrelor-Induced Angioedema: A Rare and Unexpected Phenomenon - Rajeev Seecheran; Valmiki Seecheran; Sangeeta Persad; Sasha Lalla; Naveen Anand Seecheran (Case Reports in Cardiology)
Angioedema can cause potentially life-threatening airway obstruction. This case report describes an exceedingly rare episode of ticagrelor-induced hypersensitivity reaction, manifesting as angioedema with periorbital and likely respiratory involvement. The heart team should be vigilant for this precarious condition which may require emergent airway management. Desensitization protocols and alternative regimens (e.g., clopidogrel, prasugrel, and addition of an adjunctive anticoagulant) should be considered when there is an absolute indication for antiplatelet therapy.